Study on the mechanical properties of lithium slag recycled fine aggregate concrete - Jun Wan; Caisen Wang; Jiongfeng Liang; Yunchen Wang (PLoS ONE, 2025)
To promote the sustainable utilization of industrial solid wastes in concrete applications, this study systematically investigates the combined use of lithium slag (LS) as a cement replacement and recycled fine aggregates (RFA) as a substitute for river sand (RS). Through experimental analysis with a fixed water-cement ratio (0.46), we evaluated the effects of varying LS content (0–40%) and RFA replacement rates (0–30%) on concrete performance. The results indicate that the optimal LS incorporation (20%) enhances compressive strength, splitting tensile strength, and flexural strength by 12.7%, 11.9%, and 9.16%, respectively, while maintaining adequate workability. In contrast, RFA addition caused a linear reduction in mechanical properties, with 30% RFA leading to a 19.07% decrease in compressive strength. However, the addition of LS effectively mitigated the performance losses induced by RFA, providing a compensatory effect. The conversion formulas established between cubic compressive strength and other mechanical parameters demonstrated high correlation coefficients, offering practical guidelines for lithium slag-recycled fine aggregate concrete (LSRFAC) applications. This dual-waste utilization strategy presents an environmentally responsible solution for construction material innovation, addressing both the recycling of industrial byproducts and the conservation of natural resources. Overall, this study provides a sustainable approach to concrete production by reducing environmental burdens and supporting the circular use of industrial and construction waste in structural engineering.